PERSPEKTIF ANAK TERHADAP RUANG (RUANG BERMAIN DI DESA FAJAR BARU KECAMATAN JATI AGUNG) - Adiansyah, Doni; Setianingrum, Lutfi; Sukmawati, Dian Prasetyaning (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) ITERA, 2023)
Every human being has rights, including children. Children's rights are clearly regulated in Law no. 35 of 2014, and internationally it is also included in the internationally recognized Convention on the Rights of the Child. One form of children's rights is the right to have an opinion and the right to their space to be creative and express themselves freely. Children's rights to space tend to be considered to have been fulfilled from the perspective of adult humans without looking directly from the children's perspective. This tendency gives rise to problems where children do not have the space they want based on their rights. This research is aimed at getting children's perspectives directly on space, to be able to see whether children's rights to their space have been fulfilled from the children's perspective. This research was conducted using a qualitative research methodology and through a naturalistic approach. The analysis used in this research is empirical induction and intentional induction analysis. From this research, the concept of the formation of children's perspectives on space was obtained, namely: Children's perspective on space is influenced by the availability of space for children, children's social interactions and games that children like which determine their space.